The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1136/tobaccocontrol-2015-052881
|View full text |Cite|
|
Sign up to set email alerts
|

Heterogeneity in the measurement and reporting of outcomes in studies of electronic cigarette use in adolescents: a systematic analysis of observational studies

Abstract: There are substantial differences in measurement and reporting of parameters across observational studies of electronic and conventional cigarette use in adolescents. These studies are at risk of reporting bias, and results are difficult to interpret. A core outcome set that should be measured and reported in all observational studies is required, using structured consensus techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…Selecting the most appropriate outcome category in which to place each reported outcome presented a challenge which is consistent with other data in the oral health field [ 23 ]. Often, this was because the outcomes were poorly defined or were closely or inter-related [ 31 ]. Instances of overlap of outcome domains also resulted from composite outcome measurement tools.…”
Section: Discussionmentioning
confidence: 99%
“…Selecting the most appropriate outcome category in which to place each reported outcome presented a challenge which is consistent with other data in the oral health field [ 23 ]. Often, this was because the outcomes were poorly defined or were closely or inter-related [ 31 ]. Instances of overlap of outcome domains also resulted from composite outcome measurement tools.…”
Section: Discussionmentioning
confidence: 99%
“…The definitions of quit intentions and attempts also vary across studies. Marked variation across studies in the measurement of adolescent e-cigarette use makes results difficult to interpret ( 26 ). Future research needs to use consistent and validated measures to assess quit intentions and attempts and to examine reasons for using e-cigarette by e-cigarette use frequency.…”
Section: Discussionmentioning
confidence: 99%
“…A study in mice has shown that inhalation of cartridge nicotine in e‐cigarette results in allergen‐induced airway inflammation and hyperresponsiveness caused by infiltration of inflammatory cells, including eosinophils, into the airway 14 . Patients who presented with respiratory complications following e‐cigarette use were found to have evidence of increased inflammation 37 . The damage and irritation caused by the contents of e‐cigarettes to the respiratory system of users, as well as the increased susceptibility to infections, provides a biologically plausible mechanism for why e‐cigarette use causes coughing in users.…”
Section: Discussionmentioning
confidence: 99%